A Case Report of Idiopathic Follicular Hyperkeratotic Spicules and Literature Review - Kanchana Leerunyakul; Phatcharawat Chirasuthat; Poonkiat Suchonwanit (Karger Publishers, 2019)
Follicular hyperkeratotic spicules is a rare skin disorder that is usually associated with multiple myeloma. The condition typically presents with tiny hyperkeratotic spicules in follicular distribution and predominantly on the face. To our knowledge, there has been one reported case of this condition without underlying disease. We herein report the second case of idiopathic follicular hyperkeratotic spicules in a 54-year-old Thai woman presenting with multiple follicular horn-like spicules on her face and neck.